Leveraging Institutional Platforms to Promote Convergence - Kumar, Shantanu (World Bank, Washington, DC, 2020)
The launch of NRLM to address rural poverty marks a paradigm shift in poverty alleviation because unlike other programs that preceded it, the NRLM focuses on training and capacity building, and enabling women to prepare and implement their livelihoods plans through own institutions and from banks. The importance of promoting convergence with other rural development programs, as well other ministries, is enshrined in the framework of NRLM.